Analysis of Electrical Field in the Travelling and Wave Deflection System - Staras, S.; Kleiza, A. (Elektronika ir Elektrotechnika, 2000)
The paper is related to deflection of electron beam in travelling-wave cathode-ray tubes. The finite-difference method is used for calculation of the strength of zero spatial harmonic in a periodic helical deflection system. The method can be applied for analysis of travelling-wave deflection systems with complicated structures